Synthesis of Some New Chiral Triazole-oxazoline Derivatives - Dong, Hong-Ru (Current Organic Synthesis, 2025)
Some new (S)-2-[1-aryl-5-methyl-1H-1,2,3-triazol-4-yl]-4-benzyl-4,5-dihydro-oxazoline were synthesized by the reaction of (S)-N-(1-hydroxy-3-phenylpropan-2-yl)-1-aryl-5-methyl-1H-1,2,3-triazole-4-carboxamides which were prepared from aromatic amine as starting materials, with p-toluenesulfonyl chloride, triethylamine and DMAP. The structures were characterized by 1H NMR, 13C NMR, MS and IR. The synthesized chiral triazole-oxazoline was used as a ligand in the Diels-Alder asymmetric catalytic reaction between 3-allyl-1,3-oxazolidin-2-ketone and 2-methyl-1,3-butadiene, using PdCl2 as catalyst. (S)-3-(4-methylcyclohexe-3-ene-1-formyl)-1,3-oxazolidin-2-one was obtained.BackgroundThe chiral triazole-oxazoline ligands are rarely reported.ObjectiveThe aim of the study was to synthsize some new chiral triazole-oxazoline ligands (S)-4-benzyl-2-(1-aryl-5-methyl-1H-1,2,3-triazole-4-yl)-4,5-dihydrooxazoline (5a-g).MethodsThe one-pot methods of oriented synthesis were adopted. This study provides a simple and effective method for the synthesis of new chiral triazole-oxazoline derivatives.ResultsThe some new chiral the triazole-oxazoline ligands (S)-4-benzyl-2-(1-aryl-5-methyl-1H-1,2,3-triazole-4-yl)-4,5-dihydrooxazoline (5a-g) were synthesized and the asymmetric Diels-Alder cyclization of 3-allyl-1,3-oxazolidin-2-ketone and 2-methyl-1,3-butadiene was catalyzed by PdCl2 using the synthesized (S)-4-triazole-oxazoline ligands.ConclusionSome new (S)-4-benzyl-2-(1-aryl-5-methyl-1H-1,2,3-triazole-4-yl)-4,5-dihydro-oxazoline was synthesized by corresponding N-[(S)-1-hydroxy-3-phenylpropan-2-yl]-1-aryl-5-methyl-1H-1,2,3-triazole-4-formamide, through one-pot oriented synthesis method. After preliminary evaluation, the chiral triazoline-oxazoline ligands, in which 1,2,3-triazole rings, like pyridine-type rings, chiral materials were saved and replace one oxazoline ring in the dioxazoline ligands for asymmetric catalytic reactions.
Keywords: aromatic amine